Dermal measurement of exposure to plant protection products: Actual hand exposure from hand washing vs. wearing cotton gloves - Kuster, Christian J.; Hewitt, Nicola J.; Hamacher, Georg (Frontiers in Public Health, 2022)
For the authorization of plant protection products, a quantitative non-dietary exposure risk assessment relies on established dermal exposure models, measured mainly using passive dosimetry. Exposure to the hands is determined via hand washing or using cotton gloves as a surrogate for skin. This study compared both methods using operator exposure data available from the Agricultural Operator Exposure Model (AOEM) project report. These data indicate that hand exposure determined using cotton gloves resulted in markedly higher exposure values for all exposure scenarios compared to those determined by hand washes. One explanation for this is that dermal uptake of the residues reduces the amount of residue that can be recovered by hand washing. Uncertainty due to dermal uptake can be addressed by either default assumptions or by specific dermal absorption data. However, this cannot solely account for the large difference observed between the values and is mainly likely to be due to the higher capacity of the cotton gloves vs. human skin to retain residues. The results further indicate that the variability between hand wash samples and cotton glove samples differs between the exposure scenarios. Hence, the level of conservatism related to the use of cotton gloves as surrogate skin remains unknown. In conclusion, this evaluation of the AOEM data indicates that the cotton glove method results in much higher levels of measured hand exposure than the hand wash method. It cannot be excluded that dermal uptake has contributed to that result. However, the findings suggest the higher retention capacity of cotton gloves vs. human skin to be the main impact parameter. The cotton glove method does not provide the results with regards to the protection level that can be expected from the use of protective gloves. Therefore, we believe that the application of the hand wash method is a more accurate measure of exposure levels, if either specific dermal absorption data or, in its absence, default assumptions are applied as adjustment factor.